1999
DOI: 10.1136/fn.80.1.f38
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure in babies of less than 32 weeks gestation in the first year of life

Abstract: Aim-To define the normal range of systolic blood pressure in a non-selective population based sample of babies of low gestation throughout early infancy. Methods-Daily measurements of systolic blood pressure were made in all the babies of less than 32 weeks gestation born in the North of England in 1990 and 1991 during the first 10 days of life. Additional measurements were obtained from 135 of these babies throughout the first year of life. Systolic pressure was measured by sensing arterial flow with a Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Several previous studies demonstrated that regardless of gestation week at birth where marked difference in BP values are observed, BP values become similar at the postconceptional age of 42 – 44 weeks ( 31 , 32 ). In agreement with previous data, the newborns from our study born more prematurely, despite having a longer postnatal age (almost 24 vs. 6 days) at the time of measurement, have not yet been able to reach BP and HR values of babies with higher gestational and lower postnatal age at the 35th postconceptional week.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies demonstrated that regardless of gestation week at birth where marked difference in BP values are observed, BP values become similar at the postconceptional age of 42 – 44 weeks ( 31 , 32 ). In agreement with previous data, the newborns from our study born more prematurely, despite having a longer postnatal age (almost 24 vs. 6 days) at the time of measurement, have not yet been able to reach BP and HR values of babies with higher gestational and lower postnatal age at the 35th postconceptional week.…”
Section: Discussionmentioning
confidence: 98%
“…Here, the 90 th percentile of HSCr values (from postnatal days 3-30) of children with an optimal two-year outcome were used to determine the serum creatinine critical values, which were then validated in a second group with the same neonatal characteristics. Thus, limits arising from intrinsic characteristics of the deceased infants within our cohort were overcome through internal validation of our critical values [ 27 ]. Importantly, risk factors for HSCr above the critical values were similar to risk factors for renal failure described in the literature [ 1 , 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Definition of critical values in the training group: To determine our critical values, we considered the highest serum creatinine values of children from the training group showing an optimal neurodevelopmental outcome at two years of corrected age. The 90 th percentile of HSCr levels from these children with an optimal neurodevelopmental outcome were then used to define critical values for each GA subgroup, as previously reported for other parameters like blood pressure [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because of physiological particulars and many comorbidity factors [3] [4] , it is difficult to define guidelines for starting phototherapy in VLBW infants. One validated method consists of analyzing data in infants with optimal outcome and then defining norms [22] . To determine the most adapted SBL for starting phototherapy in infants under 1001 g, we compared the 95 th percentile of SBLs in infants with optimal neurological outcome in relation to birthweight.…”
Section: Discussionmentioning
confidence: 99%